The Influence of the Board of Directors, Audit Committee, and Bank Size on Financial Performance with Leverage as a Moderating Variable - Alina Indra Sakti Dwijayanti; C. Tri Widiastuti; Prianka Ratri Nastiti (Cahaya Abadi Publisher, 2026)
The impact of the audit committee, board of directors, and bank size on the return on assets (ROA) of banks listed on the Indonesian stock exchange between 2020 and 2024 is examined in this study. As a moderating variable, the leverage ratio is investigated. Purposive sampling and a quantitative technique were used to choose 27 businesses. Simple regression analysis and moderated regression analysis (MRA) in SPSS 26 were used for the analysis. The findings indicate that whereas audit committee size has a negative, but not statistically significant, link with ROA, board size has a substantial positive correlation with ROA. Larger banks are not always more lucrative since there is a strong negative correlation between bank size and ROA. The moderation analysis's findings imply that the leverage ratio has a stronger impact on debt-intensive companies and magnifies the favorable correlation between board size and ROA. Additionally, the debt ratio was discovered to be an independent moderating factor between bank size and ROA as well as between the audit committee and ROA.